2023
DOI: 10.1101/2023.11.28.569085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral Fentanyl Consumption and Withdrawal Impairs Fear Extinction Learning and Enhances Basolateral Amygdala Principal Neuron Excitatory-Inhibitory Balance in Male and Female Mice

Anthony M. Downs,
Gracianne Kmiec,
Zoé A. McElligott

Abstract: The number of opioid overdose deaths has increased over the past several years, mainly driven by an increase in the availability of highly potent synthetic opioids, like fentanyl, in the illicit drug supply. While many previous studies on fentanyl and other opioids have focused on intravenous administration, other routes of administration remain relatively understudied. Here, we used a drinking in the dark (DiD) paradigm to model oral fentanyl self-administration using increasing fentanyl concentrations in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…One prior study demonstrated that mice maintained stable levels of oral fentanyl consumption and showed a significant preference for the active lever associated with fentanyl in an operant chamber (63). Another study utilized a drinking in the dark paradigm to model oral fentanyl self-administration in mice, finding that mice consumed increasing amounts of fentanyl as the dose increased (37). Leonardo et al (33) successfully established fentanyl IVSA in mice, showing rapid acquisition and a dose-responsive curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One prior study demonstrated that mice maintained stable levels of oral fentanyl consumption and showed a significant preference for the active lever associated with fentanyl in an operant chamber (63). Another study utilized a drinking in the dark paradigm to model oral fentanyl self-administration in mice, finding that mice consumed increasing amounts of fentanyl as the dose increased (37). Leonardo et al (33) successfully established fentanyl IVSA in mice, showing rapid acquisition and a dose-responsive curve.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is critical to establish models of FUD in mice, including IVSA models. A previous study showed that mice are capable of initiating IVSA of fentanyl (33), and other mouse models have demonstrated withdrawal symptoms following oral or vapor self-administration (36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%